Investigating the effects of urban input on the abundance and diversity of potential bio-floc forming bacteria in the River Murray, South Australia. Issue 1 (June 2020) - Kurniawan, K; Wheeler, R; Dann, L M; Mitchell, J G
Abstract: Identifying members of the aquatic microbial community and their biotic and abiotic interactions are the first step in developing inocula for bio-floc starters used as aquaculture fish-feed. This research aims to identify whether a freshwater river with urban input can be used as a source of potential bio-floc forming bacteria. To identify the bacteria, 16S rDNA sequencing was performed, to determine the taxonomy and flow cytometry was employed to enumerate bacterial abundance. To resolve the complex interactions among microbes, microbial interaction networks were produced at the family level. Actinobacteria was found to be the most abundant bacterial phylum followed by Proteobacteria, Acidobacteria, and Chloroflexi that suggested the river was in health condition. Microbial interaction networks revealed nutrients, particularly nitrate, nitrite, ammonia, and silica, are crucial in maintaining network interactions, suggesting that urban nutrient input likely shapes the riverine microbial community. The families Actinomycetales F-ACK-M1, Rickettsiaceae, Betaproteobacteria O- SBla14 and Anaerolineae O-GCA004 demonstrated greatest network centrality, each interacting with seven first-neighbor taxa, suggesting an importance in community structure. Acetobacteraceae and Chloroflexi F-Dolo23 also exhibited network centrality and were directly linked to nitrate and nitrite, suggesting they play key roles in nitrogen cycling. Propionibacterium (44.82%) was the most dominant genera found in the Murray River followed by Anaerococcus (2.94%), and Finegoldia (2.05%) . Comparison of the bacterial community comprising bio-floc and those found in the River Murray revealed that seven bacterial phyla including Proteobacteria, Bacteriodetes, Cyanobacteria, Actinobacteria, Planctomycetes, Verrumibrobia, and Chloroflexi common to bio-floc contributed to 95.8% total relative abundance in the river. However, based on genera level, there were14 bacteria genera in the river that generally present in bio-floc forming bacteria identified across all river samples constituted 4.63%. The potential bio-floc forming bacteria found mainly in downstream of the river provided various functions in the bio-floc system including producing natural flocculants to form microorganisms aggregates, a source of potential probiotics and prebiotics, nitrite oxidation and denitrification process, and degradation of organic matters.